2016
DOI: 10.1080/13880209.2016.1207090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of the antiglycative and cardioprotective activities ofPsidium guajavaleaves in the rat diabetic myocardium

Abstract: Context: Antiglycative potential of Psidium guajava L. (Myrtaceae) leaves has been established. However, the molecular basis of its antiglycative potential remains unknown. Objective: The ethyl acetate fraction of P. guajava leaves (PGEt) was evaluated to determine the cardioprotective effect and its mechanism of action compared to quercetin. Materials and methods: After the induction of diabetes by streptozotocin (55 mg/kg body weight), PGEt and quercetin (50 mg/kg body weight) was administered for 60 days. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…After the induction of diabetes by STZ (55 mg/kg) in female Sprague Dawley rats, QCT or Psidium guajava extract, respectively, was administered for 60 days. Both treatments were accompanied with decreased levels of AGEs (advanced glycation end products) in the diabetic heart suggesting beneficial cardiac effects of QCT in diabetic subjects [106]. Moreover, cardioprotective effects of QCT and rutin (QCT derivative) were documented in I/R-induced myocardial infarction in both normal and diabetic rats.…”
Section: Role Of Comorbidities In Cardioprotection By Qct and Its Dermentioning
confidence: 95%
See 1 more Smart Citation
“…After the induction of diabetes by STZ (55 mg/kg) in female Sprague Dawley rats, QCT or Psidium guajava extract, respectively, was administered for 60 days. Both treatments were accompanied with decreased levels of AGEs (advanced glycation end products) in the diabetic heart suggesting beneficial cardiac effects of QCT in diabetic subjects [106]. Moreover, cardioprotective effects of QCT and rutin (QCT derivative) were documented in I/R-induced myocardial infarction in both normal and diabetic rats.…”
Section: Role Of Comorbidities In Cardioprotection By Qct and Its Dermentioning
confidence: 95%
“…In addition, ameliorated histopathological changes, oxidative stress, inflammation and apoptosis levels were observed [103]. In the study of Soman et al [106], it was found that pure QCT (50 mg/kg) as well as extract from Psidium guajava (a plant highly enriched with QCT) showed beneficial effects on the diabetic heart. After the induction of diabetes by STZ (55 mg/kg) in female Sprague Dawley rats, QCT or Psidium guajava extract, respectively, was administered for 60 days.…”
Section: Role Of Comorbidities In Cardioprotection By Qct and Its Dermentioning
confidence: 96%
“…Translocation of NFκB, and expression of TGF-β1, CTGF, and BNP In vivo [43] Cardioprotective effects restoring plasma thyroid hormone levels and attenuating oxidative stress in the heart…”
Section: Role Mode Referencementioning
confidence: 99%
“…The synthesis of BNP induced by mechanical stress on cardiomyocytes is most likely achieved by the mechanical stress-induced synthesis of ET-1 [14,15,16,17]. ET-1 can also lead to myocardial fibrosis by stimulating transforming growth factor-beta 1 (TGF-β1), which plays a vital role in the occurrence and development of cardiac diseases such as cardiomyopathy, heart valve disease, and arrhythmias [18,19,20]. In the hearts of newborn mice, hypoxia can induce TGF-β1 to activate various signaling pathways that act on the promoter of BNP, eventually activating the expression of BNP [21].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, BNP can inhibit cardiac fibroblasts by blocking TGF-β1/Smad signaling [22]. Coinstantaneous upregulated TGF-β1 and BNP during myocardial remodeling in rats also indicates a possible relationship between these factors [20,22].…”
Section: Introductionmentioning
confidence: 99%